Strategi Kemandirian Sosial dan Ekonomi bagi Perempuan Pascaperceraian di Kota Makassar - Rijal, Muh; Indriani; Hudayah Sulaiman; A. Hardiyanti; Muis, Nurhasni (Equilibrium: Jurnal Pendidikan, 2025)
Divorce not only changes the legal status of a couple, but also impacts the social and economic conditions, especially for a woman who has experienced a divorce “post-divorce”. The women who have recently divorced often face significant changes in their economic capacity, social networks, and access to resources. This condition then encourages them to develop strategies to become independent socially and economically. This study aims to analyze how women develop their strategies for being independent in social and economic aspects after post-divorce in Makassar City. This study used a descriptive qualitative method by using a purposive sampling technique, where five females who had been divorced for two years became the informants. The data collection was conducted through observation and in-depth interviews. The results shows that post-divorce women implemented two forms of economic strategies, namely (1) independent strategies based on microbusiness such as they were selling some foods and fried foods, and work strategies in the informal service sector such as working as laundry employees and Sales Promotion Girl for cosmetics (2) In the social aspect, the informants were actively in community group activities and reconstruct their self-confidence to maintain their survival. (3) Factors supporting their independence came from strong family support and individual psychological control. Meanwhile, the inhibiting factors faced include low levels of education, and they faced a double burden of earning money and parenting.   Keywords: Post-divorce women; Economic independence; Social independence; Makassar City.